Przegląd metod pomiaru i oceny zmian strukturalnych w gospodarce narodowej oraz polityce strukturalnej Unii Europejskiej - Ładysz, Jerzy (Survey of Measurement and Evaluation Methods of Structural Changes in Domestic economy and in the European Union Structural Policy, 2008)
Conducted research aimed to present the methods of measurement and evaluation of: a) structural changes of national economy and b) structural changes of economies of states being embraced by the structural policy of the European Union. The article presents selected structural indicators, inter alia: measures of qualitative and quantitative structural changes, indicators of changes of selected economic structures. The examples of synthetic measures of structures changeability have been given. Also there were analyzed indicators of structural changes and indicators used in project evaluation in structural policy of the European Union.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 208-218